2021 European Control Conference (ECC) 2021
DOI: 10.23919/ecc54610.2021.9655122
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Structure Preserving Impedance Control of Bidirectional Antagonistic Variable Stiffness Actuation

Abstract: We propose an impedance controller for articulated soft robots implemented by bidirectional antagonistic variable stiffness (BAVS) actuation, where two motors are connected via nonlinear elastic elements to a single link allowing for a joint stiffness modulation. Naturally, the highly elastic elements introduce undesired oscillatory dynamics into the plant. To address this problem, we present a controller that allows to impose a desired link-side stiffness and damping behavior while preserving the intrinsic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…However, we showed that the origin x = 0 is a uniformly asymptotically stable equilibrium point of the closed-loop system ( 24)-( 26). Regulation [18] Tracking Desired Regulation [18] Tracking…”
Section: Stability Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…However, we showed that the origin x = 0 is a uniformly asymptotically stable equilibrium point of the closed-loop system ( 24)-( 26). Regulation [18] Tracking Desired Regulation [18] Tracking…”
Section: Stability Analysismentioning
confidence: 99%
“…The modal damping factors were chosen as ξ q = 0.2 and ξ η,i = 0.1. To demonstrate the benefits of the proposed tracking controller, a comparison with the regulation controller [18] has been performed. For the sake of comparability the parameters K q , ξ q , ξ η,i and the scaling factor for the motor inertia shaping were always chosen equal for both the regulation and the tracking controller.…”
Section: Experimental Validationmentioning
confidence: 99%
See 3 more Smart Citations